(untitled) (Web of Teachers: Inderscience Research, 2024)
The article under discussion depicts characteristic features of the linguistic personality of students as bearers of the student sociolect. The author of the article considers that youth communication allows for a completely new level of interaction, often bypassing traditional sentence structures and grammatical foundations. This indicates that young people can converse more freely and understand each other with half-words. It is also important to note that the student sociolect is continuously evolving, with new expressions emerging that quickly gain popularity and are actively used in speech.